PENERAPAN STRATEGI KOMUNIKASI INTERPERSONAL SANGGAR SENI SABA SARI DI DESA SABA KECAMATAN BLAHBATUH KABUPATEN GIANYAR DALAM PEMBERTAHANAN DI ERA PANDEMI COVID-19 - I Gusti Ngurah Agung Panji Tresna; I Gusti Ngurah Pertu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Sanggar Seni Saba Sari has certainly experienced various long journey to be able to continue to exist in maintaining the existence of the Sanggar Seni Saba Sari, especially in maintaining the Legong Bapang Gaya Saba Dance which is an icon of this sanggar. In the process, the strategy of maintaining until it continues to exist certainly deserves attention, so that researchers are interested in conducting a more in-depth review of how the Sanggar Seni Saba Sari retention strategy is in the Era of the Covid-19 Pandemic. This research uses two theories. First, The theory of systems according to Karl Weick and the theory of interpersonal communication strategies according to Joseph A. Devito. The results show that Weick's theory (1) allows members of the organization to recreate their environment by determining and negotiating a special meaning in dealing with an event, (2) assisting in the process of collecting data and information so that it can be processed and adjusted into applicable rules, (3) assist in the process of deepening information through a retention strategy in the hope of helping the organization retain information about how the organization responds in dealing with situations. Devito's theory of interpersonal communication produces a positive stimulus for each individual in an organization that plays a very important role in building awareness in creating effective communication situations while also playing a role in improving morality in the form of behavior, action, and intellectuality between communicators and communicants.